2018
DOI: 10.1109/tgrs.2017.2750491
|View full text |Cite
|
Sign up to set email alerts
|

Improving Mesoscale Altimetric Data From a Multitracer Convolutional Processing of Standard Satellite-Derived Products

Abstract: Résumé-Multi-satellite measurements of altimeter-derived Sea Surface Height (SSH) have provided a wealth of information on the ocean. Yet, horizontal scales below 100km remain scarcely resolved. Especially, in the Mediterranean Sea, an important fraction of the mesoscale range, characterized by a small Rossby radius of deformation of 15-20 km, is not properly retrieved by altimeter-derived gridded products. Here, we investigate a novel retreatment of AVISO products with a view to resolving the horizontal scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…We also demonstrate that AnDA can embed complementary variables in a simple manner through the regression variables used in the locally-linear analog forecasting operator. In agreement with our recent analysis [17], we demonstrate that the additional use of large-scale SLA information may further improve the reconstruction performance for fine-scale structures.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…We also demonstrate that AnDA can embed complementary variables in a simple manner through the regression variables used in the locally-linear analog forecasting operator. In agreement with our recent analysis [17], we demonstrate that the additional use of large-scale SLA information may further improve the reconstruction performance for fine-scale structures.…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, a significantly greater improvement is obtained when adding the true low-resolution information. The mean results are in accordance with [17], which reported that large-scale SLA information was more informative than SST to improve the reconstruction of the SLA at finer scales. Though mean statistics over one year leads to rather limited improvement, daily RMSE time series ( Figure 6) reveal that for some periods, for instance between day 130 and 150, relative improvements in terms of RMSE may reach 10% with the additional information brought by the large-scale component.…”
Section: Pb-anda Models With Auxiliary Variablessupporting
confidence: 90%
See 2 more Smart Citations
“…The application of the proposed framework to other sea surface geophysical tracers, including multi-source and multi-modal interpolation issues is considered as our first priority. SLA (Sea Level Anomaly) fields could provide an interesting case-study as the associated space-time sampling is particularly scarce and multi-source strategies are of key interest [40]. Improving the formulation and training of the covariance model is also an important issue.…”
Section: Resultsmentioning
confidence: 99%